ChemInform Abstract: Microwave‐Promoted Regio‐ and Stereoselective Vinylation of Heterocyclic Thiols. Issue 45 (23rd October 2014) - Rajesh, Nimmakuri; Sarma, Rupam; Prajapati, Dipak
Abstract Microwave promoted hydrothiolation of activated terminal alkyne (II) with hetaryl and aryl sulfides offers a convenient synthesis of vinyl sulfides in short reaction times.